Avaliação da revegetação da mata de galeria no entorno do reservatório de água da fazenda Mandaguari em Indianópolis, MG - Lima, Julia Araujo de (2007)
The degraded gallery forest that border water courses are areas that demand priority for the actions of revegetation. These bushes have a strategical paper in the conservation of biodiversity, protection of water courses against sediments deposition and contamination with agricultural defensives, in the preservation of water quality and formation of ecological corridors. The objectives of the work had been to study models and species implanted in revegetation of area permanent protection around water reservoir of Mandaguari farm in Indianópolis, MG and to indicate inside of each model, species of bigger growth and capacity of survival. For this, monthly collections of the vegetative part of flowery and/or borne fruit and taken large shrubs individuals for the herbário for identification of species had been made. Of these, some species had been chosen that had been implanted in revegetation models. The seeds had been collected, identified and led to the germination chamber. After emission of radícula had been to plântulas transplantadas for plastic and cultivated bags in fishery until beginning of rains, that implanted in definitive place in different models varying the abundance, wealth and diversity. The initial stage they had been evaluated the percentage of survival 48 species, the index of diversity for models and development of changes in the first year. The analysis used statistics was test of t Student the 0,05 of probability to compare the diversity indices. This initially between the models it varied of 3,2 the 3,5 not differing estatisticamente. The Aegiphila sellowiana and Guazuma ulmifolia had been to the species that had presented optimum development in height and diameter. However, the species Ormosia arborea, Anadenanthera colubrine, Aspidosperma tomentosum and Zanthoxylum rhoifolium had gotten survival in field better. It is concluded that used methodology revealed efficient for a small course of water and with little area of permanent preservation protege, as in the studied situation. In bigger area plantation of species with low index of mortality and adequate fertilization are indicated.